Role of TNF-α in Regulating the Exercise Pressor Reflex in Rats With Femoral Artery Occlusion - Xing, Jihong; Lu, Jian; Li, Jianhua (Frontiers in Physiology, 2018)
Responses of sympathetic nerve activity and arterial blood pressure are augmented during activation of the exercise pressor reflex in rats with femoral artery occlusion. The present study examined the role played by pro-inflammatory tumor necrosis factor-α (TNF-α) in regulating augmented sympathetic responsiveness induced by stimulation of muscle metabolic receptors and static muscle contraction following 72 hours of femoral artery occlusion. We first observed that the levels of TNF-α and protein expression of TNF-α receptor type 1 (TNFR1) were increased in the dorsal root ganglion (DRG) of hindlimbs with femoral artery occlusion. Note that TNF-α was observed within DRG neurons of C-fiber afferent nerves. Capsaicin (TRPV1 agonist) and AITC (TRPA1 agonist) were injected into arterial blood supply of the hindlimbs to stimulate metabolically sensitive thin-fiber muscle afferents. The effects of these injections on the sympathetic and pressor responses were further examined in control rats and rats with femoral artery occlusion. As TNF-α synthesis suppressor pentoxifylline (PTX) was previously administered into the hindlimb with femoral artery occlusion, sympathetic and pressor responses induced by capsaicin and AITC were attenuated. In occluded rats, PTX also attenuated the exaggeration of blood pressure response induced by muscle contraction, but not by passive tendon stretch. Overall, the results suggest that TNF-α plays a role in modulating exaggerated sympathetic nervous activity via the metabolic component of the exercise pressor reflex when the hindlimb muscles are ischemic in peripheral arterial disease.